Nanoarchitectured Structure and Surface Biofunctionality of Mesoporous Silica Nanoparticles - Kankala, Ranjith Kumar; Han, Ya‐Hui; Na, Jongbeom; Lee, Chia‐Hung; Sun, Ziqi; Wang, Shi‐Bin; Kimura, Tatsuo; Ok, Yong Sik; Yamauchi, Yusuke; Chen, Ai‐Zheng; Wu, Kevin C.‐W. (Advanced materials (Weinheim), 2020)
Mesoporous silica nanoparticles (MSNs), one of the important porous materials, have garnered interest owing to their highly attractive physicochemical features and advantageous morphological attributes. They are of particular importance for use in diverse fields including, but not limited to, adsorption, catalysis, and medicine. Despite their intrinsic stable siliceous frameworks, excellent mechanical strength, and optimal morphological attributes, pristine MSNs suffer from poor drug loading efficiency, as well as compatibility and degradability issues for therapeutic, diagnostic, and tissue engineering purposes. Collectively, the desirable and beneficial properties of MSNs have been harnessed by modifying the surface of the siliceous frameworks through incorporating supramolecular assemblies and various metal species, and through incorporating supramolecular assemblies and various metal species and their conjugates. Substantial advancements of these innovative colloidal inorganic nanocontainers drive researchers in promoting them toward innovative applications like stimuli (light/ultrasound/magnetic)‐responsive delivery‐associated therapies with exceptional performance in vivo. Here, a brief overview of the fabrication of siliceous frameworks, along with discussions on the significant advances in engineering of MSNs, is provided. The scope of the advancement in terms of structural and physicochemical attributes and their effects on biomedical applications with a particular focus on recent studies is emphasized. Finally, interesting perspectives are recapitulated, along with the scope toward clinical translation. Mesoporous silica nanoparticles (MSNs) have garnered enormous interest owing to their highly advantageous physicochemical and morphological attributes. Collectively, progression has been made by modifying the surface of the siliceous frameworks through incorporating diverse supramolecular assemblies. An overview of the fabrication of MSNs and discussions on significant advances in engineering of MSNs, along with their scope toward clinical translation, is provided.